A socio-rhetorical analysis of the Lukan narrative of the Last Supper. - Megbelayin, Ibitolu Oluseyi Jerome. (University of Ottawa (Canada), 2002)
In light of socio-rhetorical criticism, Luke's LS account emerges as rhetorical discourse both by its many Hellenistic rhetorical features and in terms of their underlying premise. Luke 22:7--38 (Western Text) clearly functions as a rhetorical discourse meant to alter the social expectations of Luke's community and produce corresponding changes in its conduct. In Chapter One, we review the history of interpretation of the Lukan LS text and provide justification for the present study. We define the aim and present our research methodology. Here we suggest that Luke achieves his self-interest, as we have defined it, by constructing his LS as a rhetorical elaboration of theme. Treating Luke's LS as a rhetorical elaboration reveals that Luke 22:7--38 (Western Text) is a unified text. In Chapter Two, we define our textual unit as the Western Text (WT) and not the Alexandrian Text (AT) of Luke's LS. Here I show how Luke crafted his elaboration by looking at the narrative material, argumentation, and repetition. Chapter Three shows that from the perspective of socio-rhetorical analysis there are four ways a text may use antecedent texts, oral or written, namely, recitation, reconfiguration, recontextualisation, and oral-scribal echo. Luke in composing his LS has reworked specific oral as well as written traditions available to him. In Chapter Four we explore Luke's dependence on the cultural systems and social structure in his contemporary Mediterranean society. This interaction with certain social codes and cultural scripts in the first-century Mediterranean leads me to conclude in Chapter Five that the language in the text can be social-culturally located as a first-century Mediterranean revolutionist response, with a conversionist tendency, that seeks to reconstruct the old social order for the purposes of establishing a new social order, the kingdom of God, the kind of primitive "Christian" community Luke describes in the first chapters of Acts. The sixth chapter explores how this social and cultural program reflects sacred interests. The concluding chapter combines exploration of the ideology of our chosen text with a resume of the course of our investigation. Our exploration of ideological texture identifies the ideology of the implied author and shows just how this ideology shapes the narrative of the Lukan LS. (Abstract shortened by UMI.)
Keywords: Religion, Biblical Studies.